Fotokatalitik prosesler ile sulu çözeltilerden 6 değerlikli krom giderimi - Çakır, Tuğba (Gebze Teknik Üniversitesi, Lisansüstü Eğitim Enstitüsü, 2019)
Bu çalışma kapsamında, laboratuvar ölçeğinde kesikli UV fotoreaktör kullanılarak UVA ışığı altında fotokatalitik oksidasyon prosesleri yardımıyla sulu çözeltilerden Cr (VI) 'nın indirgenmesi incelenmiş ve reaksiyon hız sabitleri hesaplanmıştır. ZnO ve TiO2'in farklı çeşitleri olan TiO2 (P25), TiO2 (TRONOX), TiO2 (KronoClean) ve TiO2 (Hombikat UV 100) fotokatalizörlerinin Cr (VI) giderimine etkisi incelenmiş ve ZnO'in % 79.0'lık giderimle en yüksek verimi sağladığı ve TiO2 (P25)'in de %78.8'le yaklaşık bir giderim davranışı sergilediği belirlenmiştir. Ayrıca, farklı ZnO katalizör yükleri kullanılarak giderime etkisi araştırılmış ve optimum fotokatalizör miktarı 1g/L olarak belirlenmiştir. pH 4, 7 ve 9'da yapılan çalışmalarda çözelti pH'sının yarı iletken üzerindeki etkisi araştırılmıştır. Buna göre, TiO2 (P25) kullanılarak yapılan çalışmalarda asidik koşulların fotokatalitik aktivite üzerinde olumlu etkisi olurken, alkali ortamın giderim verimini düşürdüğü gözlenmiştir. ZnO asidik ortamda çözündüğünden, sadece pH 7 ve 9'da çalışılmış ve optimum verim pH 7'de elde edilmiştir. Ancak, pH 9'da ZnO, TiO2 (P25)'e göre daha iyi Cr(VI) giderim verimi sağlamıştır. Farklı Cr(VI) başlangıç konsantrasyonlarında (5, 10 ve 15 mg/L) yürütülen çalışmalarda ise Cr (VI) konsantrasyonun artmasıyla fotokatalitik giderim veriminin azaldığı ve azalan hız sabitleriyle beraber daha uzun ışınlama süresi ihtiyacı doğurduğu görülmüştür. Ayrıca reaktördeki çözelti ortamına hava beslemesi durdurulduğu zaman giderim veriminin olumsuz yönde etkilendiği ve verimin %100'den %66'ya düştüğü görülmüştür.

In this study, the reduction of Cr (VI) from aqueous solutions by using photocatalytic oxidation processes under UVA light was investigated by using batch UV photoreactor at laboratory scale and the reaction rate constants were evaluated. The effect of ZnO and different types of TiO2 photocatalysts, which were TiO2 (P25), TiO2 (TRONOX), TiO2 (KronoClean) and TiO2 (Hombikat UV 100), on Cr (VI) removal was investigated and it was determined that ZnO had the highest yield with removal of 79.0 % and TiO2 (P25) had a similar removal effect with 78.8 %. In addition, the effect of different ZnO catalyst loadings on Cr (VI) reduction was investigated and the optimum photocatalyst amount was determined as 1 g/L. Meanwhile, the effect of solution pH on semiconductor surface was investigated in studies conducted at pH 4, 7 and 9. Accordingly, in studies worked with TiO2 (P25), acidic conditions had a positive effect on photocatalytic activity, while it was observed that alkaline solution reduced removal efficiency. Since ZnO was dissolved in acidic medium, it was studied only at pH 7 and 9 and optimum yield was obtained at pH 7. However, at pH 9, ZnO provided better Cr (VI) removal efficiency than TiO2 (P25). In studies conducted at different Cr (VI) initial concentrations (5, 10 and 15 mg/L), it was observed that with increasing Cr (VI) concentration, photocatalytic removal efficiency decreased and the need for longer irradiation time with decreasing rate constants was acquired. On the other hand, when the air supply to the solution medium in the reactor was stopped, the removal efficiency was negatively affected and the yield decreased from 100% to 66%.
Photocatalytic reduction of Cr(VI) in aqueous solutions
Keywords: Çevre Mühendisliği; Environmental Engineering